Third Five Year Plan Annual Progress Report 1963-64 Nagaland. - Planning Commission (Planning Commission, 1963)
Nagaland is Primarily Dependent on Agriculture. It has no Major or Medium Industries of Any Kind Except the Local Small Enterprises Like a Printing Press, Saw Mill, Rice Mil Etc., and Village and Cottage Industries Including Weaving. These Industries Third Contribute Towards, The Economic Growth of The Area except through the Government Projects and Schemes Under the Third Five Year Plan.
Government of Nagaland, Planning and Coordination Department